2020
DOI: 10.1021/acsomega.9b03353
|View full text |Cite
|
Sign up to set email alerts
|

Band Alignments of Ternary Wurtzite and Zincblende III-Nitrides Investigated by Hybrid Density Functional Theory

Abstract: Band gaps and electron affinities of binary and ternary, wurtzite (wz-) and zincblende (zb-) III-nitrides are investigated using a unified hybrid density functional theory, and band offsets between wz- and zb- alloys are calculated using Anderson’s electron affinity model. A conduction (and valence) band offset of 1.85 (0.89) eV has been calculated for zb-GaN/InN heterojunctions, which is 0.25 eV larger (and 0.26 eV smaller) than that of the wz- counterpart. Such polarization-free zb-GaN/InGaN/GaN quantum well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…The electronic band structure of the Al x Ga 1−x N alloys is changed with the Al composition. The bandgap dependence on the composition is almost linear between the values of the binaries -3.4 eV (GaN) and 6.0 eV (AlN) [66]. However, at x = 0.09, the order of the valence bands is changed from Γ 9 , Γ 7+ , Γ 7− to Γ 7 +, Γ 9 Γ 7− [67] which has a significant effect on the emission polarization in deep ultraviolet light-emitting diodes (DUV-LEDs).…”
Section: Crystal Structure and Electronic Propertiesmentioning
confidence: 96%
“…The electronic band structure of the Al x Ga 1−x N alloys is changed with the Al composition. The bandgap dependence on the composition is almost linear between the values of the binaries -3.4 eV (GaN) and 6.0 eV (AlN) [66]. However, at x = 0.09, the order of the valence bands is changed from Γ 9 , Γ 7+ , Γ 7− to Γ 7 +, Γ 9 Γ 7− [67] which has a significant effect on the emission polarization in deep ultraviolet light-emitting diodes (DUV-LEDs).…”
Section: Crystal Structure and Electronic Propertiesmentioning
confidence: 96%
“…Sun and co-workers [15] estimated a band gap of 1.64 eV based on the bowing parameters from literature. Tsai and Bayram [51] reported a KS gap of 1.57 eV for the ternary wurtzite-based nitride In 0.5 Ga 0.5 N, which has the same chemical composition as the (1:1) SL. Again, the best match to HSE06 (1.46 eV) among the considered XC functionals is achieved while using the optimized U-values obtained in this work.…”
Section: Transferability Check: 1:1 Inn/gan Superlatticementioning
confidence: 99%
“…19 Our device (Supporting Information A), highlighted in Figure 1(a), includes a current path consisting of a maximum SB of 1.65 eV (Figure 1 11 and Chen et al, who reported 56 kΩ/sq for 12 nm AlGaN. 12 Using p-InGaN is a major contributor to the reduction of the contact resistivity because the conduction band offset between GaN and InN is 1.6 eV, 20 leading to an electron affinity of InN of 5.91 eV, higher than any metal work-function. The ternary compound of p-GaN and InN has an estimated valence band offset of 1.15 eV 20 that should reduce the resistance between metal and 2DHG significantly.…”
mentioning
confidence: 92%
“… 12 Using p-InGaN is a major contributor to the reduction of the contact resistivity because the conduction band offset between GaN and InN is 1.6 eV, 20 leading to an electron affinity of InN of 5.91 eV, higher than any metal work-function. The ternary compound of p-GaN and InN has an estimated valence band offset of 1.15 eV 20 that should reduce the resistance between metal and 2DHG significantly. The values of resistivity obtained in this study vary from ρ c ≈ 5.6 × 10 –4 Ω cm 2 (16 nm) to ρ c ≈ 5.1 × 10 –4 Ω cm 2 (30 nm) and show a relative independence to thickness of u-GaN, in Figure 2 (c), contrary to the reported trend from the figure in the abstract.…”
mentioning
confidence: 99%